(untitled) (Discourse of Law and Administration, 2023)
This article will present selected issues related to the issue of ratification of treaties and their publication on the example of solutions in force in the Republic of Poland. It turns out that some of the existing solutions may be unconstitutional, and others – in the absence of their clarification – caused (and cause) difficulties in applying the law in practice. This can have a negative impact on the perception of Polish as a serious partner in international relations. For this reason, there is a need to amend the Act on Treaties and even the Constitution itself, in order to make the process of introducing ratified treaties into the Polish legal order more precise and to facilitate the application of international law.